Estimates for the Commutators of p-Adic Hausdorff Operator on Herz-Morrey Spaces - Naqash Sarfraz; Amjad Hussain (Mathematics, 2019)
In this paper, we investigate the boundedness of commutators of matrix Hausdorff operator on the weighted p-adic Herz-Morrey space with the symbol functions in weighted central bounded mean oscillations (BMO) and Lipschitz spaces. In addition, a result showing boundedness of Hausdorff operator on weighted p-adic <semantics> λ </semantics> -central BMO spaces is provided as well.